Effects of Sun and Oven Drying on The Physicochemical Composition of Indonesian Sandfish (Holothuria scabra) - Fitri, Dian Arsita; Purwanti, Nanik; Nursid, Muhammad; Patantis, Gintung (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Sandfish (Holothuria scabra) is a type of sea cucumber with high economic value. Sandfish are potentially used as food, pharmaceutical, and cosmetic ingredients. This research aimed to determine the effects of sun and oven drying on the physicochemical composition of sandfish collected from Pesawaran Waters, Lampung, Indonesia. The physicochemical composition includes the proximate composition, saponin content, collagen content, and metabolite profiles. The sea cucumbers were divided into two groups; the first group was boiled for 30 minutes, whereas the second group was unboiled. The sea cucumbers were oven-dried (temperature 60 °C for 24 h) and sun-dried (3 days from 08:00 a.m. until 5:00 p.m.). Fresh sandfish (without drying) were used as control samples. The dried and fresh sandfish were analyzed for their proximate composition (moisture, ash, fat, protein, and carbohydrates) and collagen content. The dried and fresh sandfish were extracted by maceration using ethanol. The extract was analyzed for its saponin content and metabolite profiles. The results showed no significant differences (p0.05) between oven-dried and sun-dried sandfish regarding their proximate composition and collagen content. However, the saponin content in boiled sandfish extract was significantly different (p0.05) from the saponin content in sandfish extract that was unboiled. The highest saponin content of all treatments was in the boiling and oven-drying treatment (N1P2), i.e., 7.418 mg quillaja/10mg extract. The Fourier Transform Infrared (FTIR) profile indicated that the functional groups in the sandfish extract did not change during the drying process. The findings indicate that oven and sun drying do not negatively affect the physicochemical composition of the sandfish, especially its bioactive compounds, i.e., saponin and collagen.